Effect of growth temperature on several exported enzyme activities in the psychrotrophic bacterium Pseudomonas fluorescens. - Gügi, B (1991)
In accordance with previous results, the activity of extracellular proteases from Pseudomonas fluorescens MF0 is maximal at a growth temperature of 17.5 degrees C, well below the optimal growth temperature. In addition, the activities of three periplasmic phosphatases display the same growth temperature optimum. Chemostat experiments have shown that it is the growth temperature itself and not the value of the growth rate that regulates these activities. In contrast, a foreign periplasmic phosphatase, expressed under the control of its own promoter, displays a different sensitivity toward temperature. We conclude that in the psychrotrophic strain P. fluorescens MF0, growth temperature exerts a specific control upon the activity of certain enzymes. The critical temperature (17.5 degrees C) is within the range of normal growth, suggesting that this control is probably different from a cold shock or heat shock response.